2018
DOI: 10.5152/tjg.2018.17582
|View full text |Cite
|
Sign up to set email alerts
|

Myotonic dystrophy type 1 and pseudo-obstruction in a child with smooth muscle α-actin deficiency and eosinophilic myenteric plexitis

Abstract: Myotonic dystrophy (MD)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Gastrointestinal symptoms were a significant comorbidity in our population. There have been previous descriptions of severe GI symptoms in DM1, including pseudo-obstruction, 19,20 and we found similar findings with three patients experiencing obstruction or pseudoobstruction. In a large cohort of 913 adult patients with DM1, 79% of patients had some GI complaint.…”
Section: Discussionsupporting
confidence: 91%
“…Gastrointestinal symptoms were a significant comorbidity in our population. There have been previous descriptions of severe GI symptoms in DM1, including pseudo-obstruction, 19,20 and we found similar findings with three patients experiencing obstruction or pseudoobstruction. In a large cohort of 913 adult patients with DM1, 79% of patients had some GI complaint.…”
Section: Discussionsupporting
confidence: 91%
“…Patients with myotonic dystrophy may have dysphagia, gastroesophageal reflux, cholecystectomy at a young age (154), or megacolon (155); in the autosomal dominant type 1 form, 70% of patients presented with these manifestations as well as malnutrition and fecal incontinence in childhood or adolescence (156). In myotonic dystrophy type 1, there are also reports of chronic intestinal pseudo-obstruction and megacolon associated with smooth muscle α-actin deficiency and inflammation of the myenteric plexus (157).…”
Section: R E V I E W S E R I E S : G U T-b R a I N A X I Smentioning
confidence: 99%
“…As previously noted, the non-specific symptoms of severe abdominal pain and distention, nausea and vomiting, constipation and/or diarrhea experienced by DM affected individuals are common and can indicate intestinal involvement in the disease. Often, the combination of these symptoms would suggest an intestinal blockage, however, early case studies of DM-affected individuals experiencing chronic diarrhea found no physical obstructions in the small or large intestine by X-ray examination [ 45 , 52 , 60 , 65 , 76 , 77 , 78 , 79 , 80 , 81 ]. Having signs and symptoms of mechanical obstruction without a physical blockage is known as pseudo-obstruction, which often occurs in the small or large intestine and results from GI dysmotility.…”
Section: Clinical Findingsmentioning
confidence: 99%
“…An intestinal permeability assay using 51CrEDTA identified altered intestinal permeability (> 3% 51CrEDTA) in 52 out of 57 DM1-affected subjects (91.22%) [ 23 ], indicating that the intestinal barrier is impaired. Intestinal dysmotility can lead to inflammation and SIBO that can impact the intestinal barrier, and while detailed descriptions of DM intestinal biopsies are lacking, samples have been remarked as having “mild, chronic inflammatory changes” [ 49 , 52 , 59 , 77 , 81 , 84 ]. Steatosis and nonalcoholic fatty liver disease (NAFLD) may also contribute to altered gut permeability [ 88 , 89 ].…”
Section: Clinical Findingsmentioning
confidence: 99%
See 1 more Smart Citation